Performance Enhancement of mm-Wave Phased Arrays for Mobile Terminals Through Grounded Coplanar Waveguide Feeding Networks With via Fences - Lee, Jae-Yeong; Choi, Jaehyun; Kim, Bumhyun; Oh, Yerim; Hong, Wonbin (Frontiers in Communications and Networks, 2021)
This paper presents a design methodology focused on feeding networks that can improve the insertion loss and coverage efficiencies of millimeter-wave (mm-Wave) phased arrays in mobile terminals. This enhancement is accomplished by using a grounded coplanar waveguide (GCPW) transmission line (TL) with via fences fabricated on single-layer FR-4 PCB. The exemplified 8-element phased arrays incorporating a compact one-dimensional electromagnetic bandgap (1-D EBG) antenna are fed through a 1×8 T-junction power divider, which includes the predetermined phased delay lines. To achieve high radiation performance with minimum leakage power or spurious waves in the T-junction power divider, an island-shape GCPW TL topology with via fences featuring high-impedance surfaces (HIS) is devised and fabricated. For further investigation on the radiation performance and spherical coverage of the mm-Wave mobile antenna, a mobile device prototype equipped with two sets of the 8-element phased arrays is prepared and studied. Through extensive simulation and experimental studies, it can be ascertained that the proposed GCPW TL topology with via fences can improve the realized gain at a coverage efficiency of 50% by more than 3 dB, between 26 GHz and 36 GHz.